Education level and disability type as causes for the discernible wage divergence for people with disabilities - Andreas Petasis (IJHCM (International Journal of Human Capital Management), 2021)
In Cyprus, disabled people face many difficulties in accessing employment, as more than 10,000 people with appropriate qualifications remain unemployed. According to worldwide estimates, disabled people receive lower wages compared to individuals without disabilities due to being either unemployed or underemployed more frequently. Using other countries with similar cultural and legal environments, this study examined the correlation between disabled people's wage levels and their disability types and educational levels. In order to gather primary data used for this correlational and regression study, 117 online questionnaire responses were collected from 6,000 registered members with physical disabilities in related organizations in Cyprus. The study examined the effect of education and disability type, on wages for disabled individuals in Cyprus using a cross-sectional survey utilizing judgment sampling (purposive sampling), in order to identify possible relationships between them, and hence see if education and disability cause a lower wage. According to the results, the two variables are not significantly associated with disability wages in Cyprus. These coefficients differ, however, between the variables 'education' and 'type of disability,' showing that in Cyprus education predicts the wage levels for disabled workers, as it is for other groups.